2019
DOI: 10.1017/s0007114519001430
|View full text |Cite
|
Sign up to set email alerts
|

Circulating calcium levels and the risk of type 2 diabetes: a systematic review and meta-analysis

Abstract: Abnormal Ca homeostasis has been associated with impaired glucose metabolism. However, the epidemiological evidence is controversial. We aimed to assess the association between circulating Ca levels and the risk of type 2 diabetes mellitus (T2DM) or abnormal glucose homeostasis through conducting a systematic review and meta-analysis. Eligible studies were identified by searching electronic database (PubMed, Embase and Google Scholar) and related references with de novo results from primary studies up to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
(175 reference statements)
0
29
1
Order By: Relevance
“…Although higher serum calcium levels have been well established as a risk factor for T2D (9)(10)(11), few studies have explored its potential association with diabetic microvascular J o u r n a l P r e -p r o o f complications. Our results suggest that higher serum calcium levels are independently associated with an increased risk of VTDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although higher serum calcium levels have been well established as a risk factor for T2D (9)(10)(11), few studies have explored its potential association with diabetic microvascular J o u r n a l P r e -p r o o f complications. Our results suggest that higher serum calcium levels are independently associated with an increased risk of VTDR.…”
Section: Discussionmentioning
confidence: 99%
“…As the most abundant mineral in the human body, calcium is also involved in biological processes such as insulin release and retinal function (5)(6)(7)(8). Several large cohort studies have associated higher serum calcium levels with a higher risk of type 2 diabetes (T2D) (9)(10)(11). Furthermore, a recent single-cell RNA sequencing study reported that calcium and other metal ion pathways are activated in proliferative DR in the J o u r n a l P r e -p r o o f mouse retina (12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the present study revealed a significant increase in plasma calcium concentrations in nontreated diabetic rats as compared to the control group. In fact, numerous studies have been reported that the high plasma calcium level was directly associated with T2D risk [ 47 , 48 ]. However, the daily coadministration of apple vinegar (2 mL/kg) was not able to ameliorate the calcium plasma level.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have warned of the adverse effects of a high calcium load. Higher circulating calcium levels have been associated with an increased risk of type 2 diabetes [ 38 ], while calcium supplements have been associated with an increased risk of myocardial infarction [ 39 ]. Nonetheless, given the much lower calcium intake in our population relative to most of the referred studies and the negative effects of lower serum calcium levels on muscle preservation, it may be reasonable to encourage increased calcium intake.…”
Section: Discussionmentioning
confidence: 99%